Heavy metal accumulation and risk assessment of lead and cadmium in cultured oysters (Crassostrea iredalei) of Cañacao Bay, Philippines - Hazell B. Valencia; Earl Jhun M. Caballar; Sjerlive Clare C. Dioneda; Jose Antonio E. Gomez; Steve Puapo Obanan (Sustinere: Journal of Environment and Sustainability, 2021)
This study analyzed the lead (Pb) and cadmium (Cd) concentrations in the water and cultured oysters (Crassostrea iredalei) of Cañacao Bay, Philippines and assessed the health risks associated with these heavy metal contaminations. Oyster and water samples from three sampling stations were collected from October 2016 to January 2017 for heavy metal analysis using inductively coupled plasma optical emission spectrometry (ICP-OES). Results showed low Pb and Cd concentrations in water and C. iredalei, which were within the maximum limits set by the Food and Agriculture Organization (FAO), Food Standards Australia New Zealand (FSANZ) and Food Safety Authority of Ireland (FSAI). Pb concentrations in oysters ranged from < 0.1 to 0.4 ± 0.1 mg/kg while Cd ranged from 0.027 ± 0.006 to 0.083 ± 0.006 mg/kg. Pb and Cd bioaccumulated in oyster tissues, but only Pb exhibited seasonal variation in concentration. The Target Hazard Quotient (THQ) and Total Target Hazard Quotient (TTHQ) were used to estimate noncarcinogenic health risks for Pb and Cd through oyster consumption. All THQs were below 1.0 indicating that there was no appreciable risk to the general population for developing noncarcinogenic effects caused by Pb and Cd in cultured oysters. Continuous monitoring of heavy metals in aquaculture areas and seafood is warranted to ensure food safety among consuming public.